A interferência do PISF na geomorfologia de rios não perenes em Pernambuco - Matos, Wérika Souza (2024)
A significant portion of the rivers in the semi-arid region is non-perennial. The irregularity of rainfall and high evapotranspiration rates contribute to an increased risk of water deficit in the region. In this context, the government aims to develop water management models to address the area's water scarcity. Among these measures, the project to transfer water from the São Francisco River, known as PISF, emerged. However, a transposition project of such magnitude generates environmental impacts, including direct and indirect effects on the rivers intersected by the project. In this sense, the research aims to highlight the hydrogeomorphological impact of PISF on the dynamics and hydrogeomorphological structure of non-perennial rivers in Pernambuco. The methodological procedures for the research were carried out based on five stages, including documentary analysis, thematic mapping, identification and spatialization of impacted rivers and structures, fluvial classification of impacted sections, and identification of hydrogeomorphological changes in the impacted sections. Ten different types of structures were identified, and these structures were observed to impact the channels differently. Structures such as gate dams, barriers, and outlet gates of barriers directly impact the channels, leading to increased sediment deposition, reduced water velocity, flooding, sedimentation processes, and erosion processes, among others. A more in-depth analysis of four representative sections identified impacts such as flow retention, channel constriction, and areas with accumulated solid material in the channels.